Effects of Ultraprotective Ventilation, Extracorporeal Carbon Dioxide Removal, and Spontaneous Breathing on Lung Morphofunction and Inflammation in Experimental Severe Acute Respiratory Distress Syndrome. (March 2015) - Güldner, Andreas; Kiss, Thomas; Bluth, Thomas; Uhlig, Christopher; Braune, Anja; Carvalho, Nadja; Quast, Theresa; Rentzsch, Ines; Huhle, Robert; Spieth, Peter; Richter, Torsten; Saddy, Felipe; et al.
<x xml:space="preserve">Abstract</x> Background: To investigate the role of ultraprotective mechanical ventilation (UP-MV) and extracorporeal carbon dioxide removal with and without spontaneous breathing (SB) to improve respiratory function and lung protection in experimental severe acute respiratory distress syndrome. Methods: Severe acute respiratory distress syndrome was induced by saline lung lavage and mechanical ventilation (MV) with higher tidal volume (VT) in 28 anesthetized pigs (32.8 to 52.5 kg). Animals (n = 7 per group) were randomly assigned to 6 h of MV (airway pressure release ventilation) with: (1) conventional P-MV with VT ≈6 ml/kg (P-MVcontr); (2) UP-MV with VT ≈3 ml/kg (UP-MVcontr); (3) UP-MV with VT ≈3 ml/kg and SB (UP-MVspont); and (4) UP-MV with VT ≈3 ml/kg and pressure supported SB (UP-MVPS). In UP-MV groups, extracorporeal carbon dioxide removal was used. Results: The authors found that: (1) UP-MVcontr reduced diffuse alveolar damage score in dorsal lung zones (median[interquartile]) (12.0 [7.0 to 16.8] vs. 22.5 [13.8 to 40.8]), but worsened oxygenation and intrapulmonary shunt, compared to P-MVcontr; (2) UP-MVspont and UP-MVPS improved oxygenation and intrapulmonary shunt, and redistributed ventilation towards dorsal areas, as compared to UP-MVcontr; (3) compared to P-MVcontr, UP-MVcontr and UP-MVspont, UP-MVPS yielded higher levels of tumor necrosis factor-α (6.9 [6.5 to 10.1] vs. 2.8 [2.2 to 3.0], 3.6 [3.0 to 4.7] and 4.0 [2.8 to 4.4] pg/mg, respectively) and interleukin-8 (216.8 [113.5 to 343.5] vs. 59.8 [45.3 to 66.7], 37.6 [18.8 to 52.0], and 59.5 [36.1 to 79.7] pg/mg, respectively) in dorsal lung zones. Conclusions: In this model of severe acute respiratory distress syndrome, MV with VT ≈3 ml/kg and extracorporeal carbon dioxide removal without SB slightly reduced lung histologic damage, but not inflammation, as compared to MV with VT = 4 to 6 ml/kg. During UP-MV, pressure supported SB increased lung inflammation.